우즈베크어권 한국어 학습자의 기계 번역기 사용 연구 : 사용 양상, 태도, 인식, 기대치를 중심으로 - 박지민; 갈라노바 딜노자; 이정희 (Foreign Languages Education, 31(1), 2024)
The purpose of this study was to examine the use of machine translation by Uzbek-speaking Korean learners, focusing on their usage patterns, attitudes, perceptions, and expectations, as well as identifying the educational implications of using machine translation. An online survey, lasting two weeks, involved 85 Korean language learners from universities in Korea and Uzbekistan. The main findings indicated a high reliance on machine translation for Korean language learning, with the majority of respondents using machine translations to find accurate vocabulary and expressions. Regarding their attitudes towards machine translation, learners mainly utilized it for literal communication, reading, and writing, and were generally satisfied with them, especially as tools for learning spellings and pronunciations. The use of machine translation significantly influenced learners’ confidence, interest in learning, and anxiety reduction. In terms of perception, learners found machine translation effective for learning Korean vocabulary, expressions, and writing, but also perceived machine translators as sources of stress and anxiety. Expectations for using machine translation were high for completing tasks in vocabulary, expression, and writing, but low for improving grammar skills and producing error-free Korean expressions.